Association of medial arch support of foot orthoses with knee valgus angle at initial contact during cutting maneuvers in female athletes: a controlled laboratory study - Toyooka, S.; Tsukada, K.; Yasui, Y.; Saho, Y.; Okawa, Y.; Ando, S.; Nakagawa, T.; Kawano, H.; Miyamoto, W. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background The effect of medial arch support foot orthoses on kinematics and kinetics of the knee joint has remained unknown.